Enhanced photovoltaic performance and thermal stability of CH3NH3PbI3 perovskite through lattice symmetrization - Shao, Feng (2020)
The organic-inorganic lead halide perovskites are attractive materials for photovoltaic application. The most widely studied perovskites based on methyl ammonium organic cation are less likely to form an ideal high-symmetry configuration at room temperature, leading to the appearance of local lattice strain. Herein, this study reports a strategy for the construction of thermally stable cubic perovskites at room temperature through the incorporation of the larger organic cation dimethyl ammonium. Detailed characterization on the single crystals and thin films reveals the formation of cubic phase with the addition of a certain amount of dimethyl ammonium at room temperature. With the presence of dimethyl ammonium, the nonradiative recombination in perovskite is suppressed, showing a longer PL lifetime and hole diffusion length. The more efficient charge extraction leads to an improvement in the photocurrent density, and then the device efficiency from 17.1% to 18.6%, together with an enhanced thermal stability at 85 °C. The influence of incorporating a larger organic cation on the structural configuration, optical properties, charge extraction, as well as the photovoltaic performance is systematically investigated, which offers an alternative way to improve the intrinsic stability of hybrid perovskites.